Pengaruh Aplikasi Gofood Terhadap Minat Konsumen Untuk Produk Makanan Dan Minuman Secara Online Menurut Model Utaut2 - Panggantara, Pang William; Sundari, Made Siti (International Conference on Multidisciplinary Issues (INCOMI), 2024)
Online transportation services are one of the applications that are widely used by the people of Indonesia, giving rise to the idea of conducting this study to analyze the effect of performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, and price value as factors that influence customer’s intention to use GoFood application to purchase food and beverage products online. This research uses a quantitative method using 100 samples data. The results of multiple linear regression analysis show that among the six variables studied, performance expectancy, social influence, hedonic motivation, and price value found to have a significant effect on customer’s intention to use GoFood application to purchase food and beverage products online, while effort expectancy and facilitating condition are found not affect customer’s intention to use GoFood application